Pulse Phytonutrients: Nutritional and Medicinal Importance - Jagdish Singh,; Rajni Kanaujia ,; N.P. Singh, (Journal of Pharmacy and Nutrition Sciences, 2016)
Pulses are important food crops which offer significant nutritional and health advantages due to their high protein content and a unique nutritional profile, i.e., low fat source of digestible protein, dietary fibre, complex carbohydrates, resistant starch and a number of essential vitamins, especially, the B-group vitamin B9 (folate). In addition to these vitamins and minerals contributing to a healthy diet, pulses contain a number of non-nutritive bioactive substances including enzyme inhibitors, lectins, saponins, phytates, phenolic compounds and oligosaccharides. The latter contributes beyond basic nutritional value and is particularly helpful in the fight against non-communicable diseases often associated with diet transitions and rising incomes. Phytic acid exhibits antioxidant activity and protects DNA damage, phenolic compounds have antioxidant and other important physiological and biological properties, and galacto-oligosaccharides may elicit prebiotic activity. Research findings on different phytochemicals in pulse seeds and their role in preventing the lifestyle diseases has been discussed. Encouraging awareness of the nutritional value of pulses can help consumers adopt healthier diets and also could be an important dietary factor in improving longevity.